ALIGNING, BREAKING OR NEGOTIATING? A CASE OF AFGHAN COMMUNITIES IN EARLY-MODERN SOUTH ASIA - Akansha Singh (International Conference on Social and Islamic Studies, 2021)
In early modern South Asia, the Afghans shared a fraught relationship with the Mughal Empire. Several Afghan groups resisted Mughal authority, while some also allied with the empire. In this context, this paper will investigate the utility of the concept of fitna in helping us make sense of this complex history. It focuses on the actions of the Afghans in relation with Mughal wars directed against them between 1585, which marked the Mughal annexation of Kabul and the beginning of Akbar’s campaigns against the Afghans of Afghanistan, and 1612—when Khwaja Usman, an important Afghan zamindar was defeated by Mughal forces in Sylhat in eastern Bengal. In this paper I also intend to ask whether the Afghans, in the late-sixteenth and early-eighteenth centuries, behaved as one community, who stuck together as a community, or operated as more splintered sub-groups. The paper will be based on two literary texts: Abul Fazl’s Akbar-nāma which is a detailed biographical account of the reign of Mughal emperor Akbar. The second is Mirza Nathan’s Bahāristān-i Gh ā’ibī. It is a neglected source on the history of the Mughal campaigns in eastern India during the early-seventeenth century. The paper will have two sections, focusing respectively on the Afghans in Afghanistan and the Afghans in Bengal. The region of Afghanistan denotes the mountainous region located roughly to the south and east of Hindu Kush and to the north and west of the Indus River. This is the earliest attested homeland of the Afghans. The part of Bengal that I have taken into consideration was known as “Bhati” or East Bengal. This area included the entire delta east of the Bhagirathi-Hooghly River and roughly corresponds with modern Bangladesh.